ACE genotype and the muscle hypertrophic and strength responses to strength training - Charbonneau, D. E.; Hanson, E. D.; Ludlow, A. T.; Delmonico, M. J.; Hurley, B. F.; Roth, S. M. (Medicine & Science in Sports & Exercise, 2008)
Purpose: Previous studies have linked an insertion/deletion polymorphism in the angiotensin-converting enzyme (ACE) gene with variability in muscle strength responses to strength training (ST), though conclusions have been inconsistent across investigations. Moreover, most previous studies have not investigated the influence of sex on the association of ACE I/D genotype with muscle phenotypes. The purpose of this study was to investigate the association of ACE genotype with muscle phenotypes before and after ST in older men and women.